(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
This paper aims to identify the role that accounting disclosure plays and its influence on the efficiency of investment decisions, and how to address the problem facing banks, and the sample of the research, which is the spread of the principle of preservation and non-accounting disclosure. The data and information are for the stakeholders and thus reflect negatively on the decision maker in making the decision. Effective investment. According to the application of the research hypothesis and the research objectives, a questionnaire form was developed consisting of three axes the first axis traded with the demographic distribution of the sample and the second axis included the dimensions of the accounting disclosure, while the second axis included the dimensions of the accounting disclosure. Third, it included the dimensions of effective investment decisions, where the five-dimensional Likert scale was used to measure the research variables and the model was distributed to the research sample, and out of 38 employees, 35 employees were recovered, and thus the response was 92%, where statistical methods such as correlation and regression coefficient were used to measure the relationship and impact. Between search variables using spss program in data analysis. In addition, efficiency of investment decisions, that is, every time a bank discloses its financial information, more decision-makers can make effective decisions. The researcher recommended that banks publish their lists periodically and honestly, expressing their true financial reality, and not tampering with numbers to increase the degree of disclosure in order to make various decisions.